STUDY WASTE BRINE USED OUTPUT SEPARATOR PLTP DIENG - Roni Hajianto, Muhamad
This research discusses the opportunity to utilize the waste brine of Dieng PLTP separator output as a new geothermal power plant using binary cycles. The initial stage of this research is to do modeling with the help of Engineering Equation Solver (EES) software. Thermodynamic analysis was performed with variations in 3 types of working fluids namely Isobutane, N-Butane and R236fa. The N-butane working fluid produces the greatest power at 532.8 kW and thermal efficiency of 14.07%. The isobutane working fluid produces a net power of 514.1 kW and a thermal efficiency of 13.56%. The working fluid R236fa produces a net power of 486 kW and a thermal efficiency of 12.82%.